Inquérito soroepidemiológico sobre a infecção chagásica em doadores de sangue na região do Alto Paranaíba, Minas Gerais - Silva, Luciana Pereira [UNESP]; Goncalves da Silva, Regildo Marcio [UNESP] (Universidade Federal de Uberlândia (UFU), 2010)
This study aimed to evaluate the seroprevalence of Trypanosoma cruzi infection in blood donors of the core of Patos de Minas Regional Foundation's Hemominas, MG. To this end, tests were used (ELISA) and Reverse Passive Hemagglutination (HPR). Through retrospective study from 1996 to 2006, was considered the result of serological 21,787 donors where 259 (1.2%) were seropositive for T. cruzi infection and the highest number of seropositivity was found in the group of 41-50 years. The total number of donors tested, 15 143 (69.5%) were male and 6644 (30.5%) females giving a seroprevalence rate of 170 (0.8%) and 89 (0.4%) respectively. This seroepidemiological survey showed that still prevail rates of transmission of Chagas disease, which reinforces the idea of the need for serological tests for the prevention of Chagas disease, especially in endemic areas as the region of Triangulo Mineiro and Alto Paranaiba.

Esse estudo tem como objetivo avaliar a soroprevalência de infecção pelo Trypanosoma cruzi em doadores de sangue do núcleo Regional de Patos de Minas da Fundação Hemominas, MG, no período de 1996 a 2006, usando os testes Ensaio Imunoenzimático (ELISA) e Hemaglutinação Passiva Reversa (HPR). Através de estudo retrospectivo no período de 1996 a 2006, foi analisado o resultado sorológico dos 21.787 doadores onde 259 (1,2%) foram soropositivos para a infecção chagásica e o maior número de soropositividade foi encontrado no grupo de 41-50 anos. Do total de doadores analisados 15.143 (69,5%) foram do sexo masculino e 6.644 (30,5%) do sexo feminino apresentando uma taxa de soroprevalência de 170 (0,8%) e 89 (0,4%) respectivamente. O inquérito soroepidemiológico mostrou que ainda prevalecem as taxas de transmissão da doença de Chagas conhecidas no Brasil.
Inquerite seroepidemiologic for chagas disease among blood donors in the region of alto Paranaiba, Minas Gerais
Keywords: Chagas' disease; Blood donors; Trypanosoma cruzi